Efeito da espessura e do envelhecimento por solução ácida de diferentes resinas compostas bulk fill nas propriedades de microdureza superficial e fluorescência - Ferreira, Lyvia Karla Cerci (2017)
The aim of this research was to compare the behavior of different thicknesses of bulk fill composite resins by analyzing the microhardness at the top and bottom of specimens (SP), the effect of aging with acid solution (ethanol / water) and fluorescence evaluation. 135 SP were fabricated with thicknesses of 2, 3 and 4 mm subdivided into 5 groups (n = 27): Z35; Aura; Tetric; SureFil; Filtek Bulk Fill (FBF). Each SP was photoactivated by LED light for 20 seconds. The microhardness test was performed after 24 hours and 30 days (ethanol / water solution) on both top and bottom surfaces. Fluorescence analysis was performed with the aid of a dark chamber by three calibrators: low, medium and high. The microhardness data were submitted to the factorial ANOVA test for Repeated Measures, followed by the LSD-Fisher follow-up test. Fluorescence by the LSD-Fisher Test. After 24h the microhardness was higher at the top in the thickness of 2mm: TETRIC and FBF, 3mm: Z350, TETRIC and FBF, 4mm: Z350, AURA, TETRIC and FBF. After aging the highest values in the bottom: 2mm: TETRIC and FBF, 3mm: AURA and TETRIC, in the 4mm: AURA was significantly higher than the first average. (p <0.05). It was possible to close that the larger the thickness, the greater the difference of the microhardness between the top and bottom surfaces. With regard to fluorescence, TETRIC (BF) was the only composite resin that did not have significantly altered values with increasing thickness. Aging in ethanol / water solution increased the microhardness values of some TETRIC, FBF and AURA composite resins.